The highwayman's footsteps - Morgan, Nicola (London : Walker Books, 2006)
High-born William de Lacey runs away from home at the age of fourteen after his father and brother denounce him as a coward, and is captured by an armed highwayman who turns out to be a girl, and together they seek vengeance against William's cruel father and the soldiers who killed the girl's parents.
Young Adult.
Young Adult
Keywords: Adventure and adventurers -- Fiction; Revenge -- Fiction; Adventure fiction; Revenge -- Fiction; Great Britain -- History -- 1760-1789 -- Fiction; Great Britain -- History -- Fiction